Homo Novus Vollendlichkeit im Zeitalter des Transhumanismus - Dürr, Oliver (STUDIA OECUMENICA FRIBURGENSIA, 2021)
Based on current and projected breakthroughs in biological, genetic, and digital technologies-and their possible convergences-contemporary transhumanism confronts the Christian faith with the question: can finite beings be saved from suffering, illness and death? Transhumanists emphatically embrace this possibility as they offer their concrete visions of a future self-redemption through science, medicine, and technology. Transhumanism aims to take control of the evolutionary process and to steer it into a better future for humanity, or rather, their artificial successors. This book is a comprehensive and constructive critique of the transhumanist agenda and its underlying sociotechnical imaginary, worldview, and anthropology. For this task, it draws on theological resources of Christian tradition(s) in novel ways that serve to render the Christian faith plausible in a digital age. In developing a theology that explores the creative potential of "perfected finitude" (Vollendlichkeit) from an eschatological perspective, it contributes to a "theology of technology".